Exploring Patterns of Absenteeism from Prekindergarten Through Early Elementary School and Their Associations With Children's Academic Outcomes - Wendy Wei (SAGE Publishing, 2024)
Using statewide administrative data from a sample of children enrolled in public prekindergarten (pre-K) programs in Massachusetts, I examined heterogeneity in children's absenteeism patterns from pre-K to Grade 3 and linked these patterns to their Grade 3 academic outcomes. After latent class growth analysis, six absenteeism patterns emerged. The vast majority of children (85%) had consistently low absenteeism, and only a small percentage of children (1%) demonstrated consistently high absenteeism. Four patterns showed variation in absenteeism over time, with two characterized by high absenteeism in only the pre-K year, another with a peak during kindergarten, and a final one with rising absenteeism across grades. Children with always low absenteeism had higher average English language arts and math scores than did children in the other patterns, and children in the two high pre-K absenteeism patterns and peak in kindergarten pattern had higher math scores than those with rising and always high absenteeism patterns.